CONTEMPORARY ISSUES ABORTION LATER DATE - Елена Николаевна Кравченко; Екатерина Валерьевна Коломбет; Лариса Владимировна Куклина (The Publishing House Medicine and Enlightenment, 2017)
Presented literature review covers issues of relevance and statistics of abortions in later stages, regulatory documents, methods of abortion in the second trimester, complications of their conduct, said the security methods of induced abortion.